Terapi Thought Stopping, Relaksasi Progresif dan Psikoedukasi terhadap Penurunan Ansietas Pasien GGK yang Menjalani Hemodialisa - Sri Atun Wahyuningsih (Jurnal Keperawatan Silampari, 2020)
This study aims to describe the management of anxiety nursing care in physically impaired patients. They receive thought to stop therapy, progressive relaxation, and psychoeducation in the Hemodialysis Room on the 3rd floor of Pelni Hospital in Jakarta. The method in this study uses the experimental process. The results of research on the response of anxiety patients after receiving therapy is a widespread patient perception, the patient's physiological response to an increase in sleep and eating, affective responses of patients do not feel worried, and patients can socialize. The practical implementation of nursing therapy packages provided on a mild scale is generalist therapy and specialist therapy of thought stopping, progressive relaxation, and psychoeducation. The result is that the patient's ability to control anxiety increases and has a positive impact on caregivers. Keywords: Anxiety, Psychoeducation, Progressive Relaxation, Thought Stopping